Export Markets and Labor Allocation in a Low-Income Country - McCaig, Brian; Pavcnik, Nina (American Economic Review, 2018)
We study the effects of a positive export shock on labor allocation between the informal, microenterprise sector and the formal firm sector in a low-income country. The United States-Vietnam Bilateral Trade Agreement led to large reductions in US tariffs on Vietnamese exports. We find that the share of manufacturing workers in Vietnam in the formal sector increased by 5 percentage points in response to the US tariff reductions. The reallocation was greater for workers in more internationally integrated provinces and for younger cohorts. We estimate the gap in labor productivity within manufacturing across the informal and formal sectors. This gap and the aggregate labor productivity gain from the export-induced reallocation of workers across the two sectors are reduced when we account for worker heterogeneity, measurement error, and differences in labor intensity of production. (JEL F16, J24, O14, O17, O19, P23, P33)